REGIONAL SECURITY COMPLEX THEORY AND SOFT POWER: MAPPING CHINA’S ENGAGEMENT IN AFGHANISTAN (Margalla Papers, 2022)
The paramount interest of China in Afghanistan seems to ensure peace and stability in the region. Beijing’s soft power approach towards Afghanistan through its neutral stance and minimum involvement in domestic politics within Afghanistan proved to be an advantage in cementing China’s role in Afghanistan as a credible mediator. China extends its influence in the region through the Belt and Road Initiative, where the importance of CPEC is interlinked with the development of China’s western sector. China aims to harness the Afghan territory for its transit routes because Afghanistan bridges the connectivity gap between Central Asia and West Asia. This paper highlights that the current interests of China in Afghanistan are multiple. China is utilizing all the soft power elements to promote and expand the areas of activities of the Shanghai Cooperation Organization to South Asia because stability in Afghanistan cannot be achieved solely. Understanding Regional Security Complex Theory and Soft Power can encapsulate China’s engagement in Afghanistan. It has made a considerable effort by highlighting regional complexities on various multilateral fronts like China-Pakistan-Afghanistan, China-Russia-Afghanistan, and China-Russia-Pakistan-Iran. This study develops an analytical framework of South Asian security from the regional point of view and analyses external powers' role in the transition of regional security complexes. Bibliography EntryTahir, Mariam. 2022. "Regional Security Complex Theory and Soft Power: Mapping China’s Engagement in Afghanistan." Margalla Papers 26 (2): 39-48.